Local communities' perspectives on ecological restoration of native plant species: Evidence from Dlhi's Suthern Rdge - Shreya Gupta; Sukanya Das; Dil Bahadur Rahut (Asian Development Bank Institute (ADBI), 2024)
Human activities and natural disturbances have significantly damaged ecosystems, resulting in a loss of biodiversity and creating a need for ecological restoration. Urban forests, in particular, are impacted by invasive species such as Prosopis juliflora, which compete with native species and disrupt ecosystem functions. Although introduced for benefits like fuelwood and desertification control, these species have turned into harmful invaders. Restoration efforts require balancing local biodiversity needs with societal values and managing conflicts among stakeholders. Understanding community perceptions of ecosystem services and disservices is crucial for effective management. This study investigates local perceptions of communities near Delhi's Southern Ridge regarding Prosopis juliflora and the willingness to pay for its biological control. Using principal component analysis (PCA), the study identified six ecosystem service (ES) and three ecosystem disservice (EDS) bundles. ES bundles were categorized using the Common International Classification of Ecosystem Services (CICES), while EDS bundles followed prior studies. The results revealed connections between biodiversity, recreational activities, and disservices such as poor visibility and connectivity. The findings also highlighted trade-offs between provisioning and regulating services, with gender-specific impacts on connectivity and accessibility. The mean and median Willingness to Pay (WTP) for ecological restoration of native plant species was also calculated for different scenarios, showing an increasing trend in mean WTP with more conservation, while median WTP showed fluctuations depending on the potential economic impact of eliminating Prosopis juliflora.
Keywords: Q57; 330; ecosystem services and disservices; ecological restoration; invasive plant species; Prosopis juliflora; contingent valuation method; urban biodiversity